ADHD Prevalence and Association with Hoarding Behaviors in Childhood-Onset OCD - Sheppard, Brooke (2010)
BACKGROUND: It has been suggested that attention-deficit hyperactivity disorder (ADHD) and obsessive-compulsive disorder (OCD), both neurodevelopmental disorders with onset in childhood, are highly comorbid, but previous studies examining ADHD and OCD comorbidity have been quite variable, partly because of inconsistency in excluding individuals with tic disorders. Similarly, ADHD has been postulated to be associated with hoarding, although this potential relationship is largely methodologically unexplored. This study aimed to examine the prevalence of ADHD among individuals with childhood-onset OCD but without comorbid tic disorders, as well as to examine the relationship between clinically significant hoarding behaviors (hoarding) and ADHD. METHOD: ADHD prevalence rates and the relationship between ADHD and hoarding were examined in 155 OCD-affected individuals (114 probands and 41 relatives, age range 4–82 years) recruited for genetic studies and compared to pooled prevalence rates derived from previously published studies. RESULTS: 11.8% met criteria for definite ADHD, while an additional 8.6% had probable or definite ADHD (total=20.4%). 41.9% of participants with ADHD also had hoarding, compared to 29.2% of participants without ADHD. Hoarding was the only demographic or clinical variable independently associated with ADHD (odds ratio=9.54, p<0.0001). CONCLUSION: ADHD rates were elevated in this sample of individuals with childhood-onset OCD compared to the general population rate of ADHD, and there was a strong association between ADHD and clinically significant hoarding behavior. This association is consistent with recent studies suggesting that individuals with hoarding may exhibit substantial executive functioning impairments and/or abnormalities, including attentional problems.